Sidetracked why our decisions get derailed, and how we can stick to the plan - Gino, Francesca (Harvard Business Review Press, 2013)
A psychologist and business professor takes an in-depth look at decision-making, explaining the pitfalls people can avoid to stay on track with their decisions and reach their goals